19th Annual U.C. Berkeley Heavy at Claremont Hotel-Berkeley - Watkins, Howard::::::::: (1987)
On floor: Terri Mesple, Alan Pricco, David Morse, Kathy Muniz, David Atkinson, Lori Beresford, Bill Walker (no tie) , John Beresford, Cynthia Nicholson and Greg Nicholson; seated: Dale Mesple, Teresa Pricco, Denise Morse, Jerry Neary (hidden), Bonnie Neary, Cathy Barkett, Joe Barkett, George Garofalo, Heidi Pieczonka Garofalo (in green dress), Janie Gumpert and Christine Watkins with Howard Watkins standing